The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.21470/1678-9741-2018-0350
|View full text |Cite
|
Sign up to set email alerts
|

"Overtime Hours Effect" on Emergency Surgery of Acute Type A Aortic Dissection

Abstract: ObjectiveTreatment of acute diseases of the aorta is still associated with high mortality and morbidity. It is believed that interventions for these diseases on overtime hours (night shifts or weekend shifts) may increase mortality. In this study, we investigated the effect of performing acute type A aortic dissection surgery on overtime hours in terms of postoperative outcomes.Methods206 patients who underwent emergency surgery for acute type A aortic dissection were retrospectively evaluated. Two groups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…We also explored the possibility of surgical teams having differing levels of experience in the IH and OOH groups. We noted that although Gokalp et al 9 was able to ensure that patients in both cohorts were operated by teams with similar levels of surgical experience, Narayan et al 12 were unable to account for the differences in surgical experience between the two groups in their study. Other studies included in this systematic review did not adequately control and report on this factor 8,10,11,13 .…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…We also explored the possibility of surgical teams having differing levels of experience in the IH and OOH groups. We noted that although Gokalp et al 9 was able to ensure that patients in both cohorts were operated by teams with similar levels of surgical experience, Narayan et al 12 were unable to account for the differences in surgical experience between the two groups in their study. Other studies included in this systematic review did not adequately control and report on this factor 8,10,11,13 .…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, 30‐day mortality rate was found to be significantly lower in the IH cohort as compared with the OOH cohort ( n = 621 in IH vs. n = 334 in OOH cohort; RR, 0.81; 95% CI [0.72, 0.90]; p = .0001; Figure 3). Also, some studies 9,13 found that the complication of AKI was significantly lower in the IH cohort as compared with the OOH cohort ( n = 120 [27%] vs. n = 144 [31%]; RR, 0.80; 95% CI [0.65, 0.98]; p = .03, Figure S9). Only two studies 9,10 reported the total hospital stay and this was not different between the IH and OOH cohorts, 11.5 ± 12.5 in IH versus 11.0 ± 14.0 in OOH (WMD, 0.71; 95% CI [−2.20, 3.62]; p = .63; Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations